Understanding the foot's functional anatomy in physiological and pathological conditions: The calcaneopedal unit concept. (April 2019) - Ghanem, I.; Massaad, A.; Assi, A.; Rizkallah, M.; Bizdikian, A. J.; El Abiad, R.; Seringe, R.; Mosca, V.; Wicart, P.
Abstract: Background: A thorough review of the available orthopaedic literature shows significant controversies, inconsistencies and sparse data regarding the terminology used to describe foot deformities. This lack of consensus on terminology creates confusion in professional discussions of foot anatomy, pathoanatomy and treatment of deformities. The controversies apply to joint movements as well as static relationships between the bones. Description: The calcaneopedal unit (CPU) is a specific anatomical and physiological entity, represented by the entire foot excepted the talus. The calcaneus, midfoot and forefoot are solidly bound by three strong ligaments that create a unit that articulates with the talus. The movement of the CPU is complex, as it rotates under the talus, around the axis of Henke that coincides with the talo-calcaneal ligament of Farabeuf. This calcaneopedal unit is deformable. It is compared with a twisted plate, able to adapt to many physiological situations in standing position, in order to acheive a plantigrade position. Moreover, the calcaneopedal unit and the talo-tibiofibular complex are interdependent; rotation of the latter produces morphologic modifications inside the former and vice versa. Purpose: This paper is a review article of this concept and of its physiopathological applications.